204k views
4 votes
Simplify the expression (4x − 3)(x + 5).

A. 4x2 − 17x + 15

B. 4x2 − 17x − 15

C. 4x2 + 17x + 15

D. 4x2 + 17x − 15

2 Answers

0 votes

D using the foil method

User Eukras
by
4.1k points
4 votes

Answer:
4x^2+17x-15

Explanation:

To simplify the given expression we need to apply the distributive property in algebra.

The distributive property is given by :


a(b+c)=ab+ac

The given expression:


(4x- 3)(x + 5)\\\\=(4x-3)x+(4x-3)5\ \ \ \ \text{By distributive property}\\\\=4x^2-3x+20x-15\\\\=4x^2+(-3+20)x-15\ \ \ \text{Combining like terms}\\\\=4x^2+17x-15

User Mogsie
by
4.6k points